How competitiveness shocks affect macroeconomic performance across euro area countries - Karsten Staehr; Robert Vermeulen (European Central Bank (ECB), 2016)
This paper considers the short-term effects of competitiveness shocks on macroeconomic performance in the euro area. Vector autoregressive models are estimated on quarterly data from 1995 to 2013 for individual countries and the whole euro area. The results show that competitiveness shocks help to explain subsequent GDP developments in most countries but have little explanatory power for the current account balance and domestic credit. These results apply for all of the competitiveness measures considered, but a non-traditional competitiveness measure accounting for quality differences fares better in some cases. The effects of the competitiveness measures vary substantially across the countries in the euro area, which likely reflects their different economic structures and institutions. This heterogeneity suggests that policy measures seeking to improve competitiveness may have very different effects on economic performance and financial stability in different countries.
Keywords: E32; E61; F32; 330; competitiveness; euro area; macroeconomic variables; transmission